Pengaruh Diferensiasi Upah Antar Propinsi Terhadap Kesempatan Kerja - Bambang Setiaji; Sudarsono - (Economic Journal of Emerging Markets, 2004)
This research aims to examine the effect of wages differentiation on employments. The policies of wages differentiation are observed from minimum sector wages which is still done in some provinces. The differentiation itself is aimed to exhaust the customer’s surplus. The research shows that the more wages differentiation the more employments will be offer¬ed. But, unfortunately some provinces still set high minimum sector wages. This case will cause negative effect on empowerment, and on the other hand in limited formal manufactur¬ing in¬dustries will reduce the gap of distribution of value added between the employers and the workers.Keywords:  wage differentiation, employment, industry, and region studies